The Effect of Green Banking Performance and Service Quality on Customer Satisfaction Using Mobile Banking - Fitri Rahmadila; Ridwansyah; Weny Rosilawati (Department of Islamic Banking, 2025)
Purpose – This inquiry aims to examine the impact of Green Banking performance and service quality on customer satisfaction using Mobile Banking. Methodology - In this inquiry using the type of primary data by survey method, which makes a questionnaire with questions related to research. The data analysis technique used is multiple linear regression analysis. This technique is useful to find out the impact of several independent elements on the dependent element analyzed through SPSS version 29. Findings – Based on the results obtained that the performance of green banking and service quality significantly affect customer satisfaction. Together, green banking performance and service quality have a significant influence on customer satisfaction using mobile banking. Implications – The results of this inquiry will provide recommendations on the association between the performance of green banking and mobile banking is increasingly crucial in the context of digital transformation in the banking sector that focuses on sustainability. Originality – This inquiry provides insights to increase attention to the concept of sustainability in the modern banking world, especially in the application of green banking.